Insulin Sensitivity Is Not Decreased in Adult Patients With Hypopituitarism Without Growth Hormone Replacement - Castillo, Alejandro Rosell; de Souza, Aglecio Luiz; Alegre, Sarah Monte; Atala, Yeelen Ballesteros; Zantut-Wittmann, Denise Engelbrecht; Garmes, Heraldo Mendes (Frontiers in Endocrinology, 2019)
Decreased insulin sensitivity in patients with hypopituitarism without GH replacement (pHP-WGHR) remains conflicting in the literature. It is known that these patients present decrease in free fat mass and increase in fat mass. Classically, this kind of alterations in body composition is associated with decrease in insulin sensitivity; however, there is no consensus if this association is found in pHP-WGHR. Thus, we investigated pHP-WGHR regarding insulin sensitivity by euglycemic hyperinsulinemic clamp, the gold standard method, and body composition. In a cross-sectional study, we evaluated 15 pHP-WGHR followed up in a Service of Neuroendocrinology and 15 individuals with normal pituitary function as a control group with similar age, gender and body mass index. Insulin sensitivity was evaluated by euglycemic hyperinsulinemic clamp and homeostatic model assessment insulin resistance (HOMA-IR). Kappa coefficient evaluated the agreement between these two methods. Percentage of fat mass, percentage of free fat mass, fat mass weight and free fat mass weight were assessed by electrical bioimpedance. The pHP-WGHR presented similar insulin sensitivity to control group by euglycemic hyperinsulinemic clamp, both by the M-value, (p=0.0913) and by the area under the glucose infusion rate curve, (p=0.0628). These patients showed lower levels of fasting glycemia (p=0.0128), insulin (p=0.0007), HOMA-IR (p=0.009). HOMA-IR shows poor concordance with euglycemic hyperinsulinemic clamp (Kappa=0.16) in pHP-WGHR, while in the control group the agreement was good (Kappa=0.53). The pHP-WGHR presented higher values of percentage of fat mass (p=0.0381) and lower values of percentage of free fat mass (p=0.0464) and free fat mass weight (0.0421) than the control group. This study demonstrated that the insulin sensitivity evaluated by euglycemic hyperinsulinemic clamp in pHP-WGHR was similar to individuals with normal pituitary function, despite the pHP-WGHR presented higher fat mass percentage. HOMA-IR was not a good method for assessing insulin sensitivity in pHP-WGHR.